In-vitro bioequivalence study of 8 brands of metformin tablets in Iran market - Parvin Zakeri-Milani, Peyman Nayyeri-Maleki, Saeed Ghanbarzadeh, Mahboob Nemati, Hadi Valizadeh (Journal of Applied Pharmaceutical Science)
Bioequivalence studies are the commonly accepted methods displaying therapeutic equivalence between two products .This study was conducted to evaluate the bioequivalence between different formulations of metformin 500 mg and 1000 mg tablets which were marketed in Iran, and innovator brand. Considering that only in vitro bioequivalence studies can predict the in vivo bioequivalence, and to save time and cost, three essential in vitro tests including assay, weight variation and a comparative in vitro dissolution study were performed. In order to compare formulations, dissolution profiles were taken and compared through two model independent methods, difference factor (f1) and similarity factor (f2). All the tested brands released more than 80% drug in 30 minutes and contained 95-96.3% of labeled amount except b and C. The acceptance value in all cases were below 15. Therefore it is evident that test products except brand C were bioequivalent to the reference product, and could be used as a generic substitute for the innovator product. Results emphasize to need for post marketing investigation for new formulations.
Keywords: Metformin tablets,Bioequivalence,In vitro,Dissolution profile.